2015
DOI: 10.1161/atvbaha.115.306460
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Psoriasis Associates With Aortic Vascular Inflammation Detected by FDG PET/CT and Neutrophil Activation in a Prospective Observational Study

Abstract: Objective To understand whether directly-measured psoriasis severity is associated with vascular inflammation assessed by 18F-fluorodeoxyglucose positron emission tomography computed tomography (FDG PET/CT). Approach In depth cardiovascular and metabolic phenotyping was performed in adult psoriasis patients (n=60) and controls (n=20). Psoriasis severity was measured using psoriasis area severity index (PASI). Vascular inflammation was measured using average aortic target-to-background ratio using FDG PET/CT.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
1
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 166 publications
(180 citation statements)
references
References 50 publications
7
164
1
5
Order By: Relevance
“…Atherosclerosis and psoriasis are chronic inflammatory diseases accompanied by changes in blood cell composition and cytokine levels. Our group has shown in the past that psoriasis has increased neutrophil cell counts, which show a direct positive association with psoriasis severity (25). The role of monocytes and their subsets in human psoriasis was highlighted in a recent publication (8), which is in accordance to our mouse data presented in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Atherosclerosis and psoriasis are chronic inflammatory diseases accompanied by changes in blood cell composition and cytokine levels. Our group has shown in the past that psoriasis has increased neutrophil cell counts, which show a direct positive association with psoriasis severity (25). The role of monocytes and their subsets in human psoriasis was highlighted in a recent publication (8), which is in accordance to our mouse data presented in this study.…”
Section: Discussionsupporting
confidence: 90%
“…In patients with psoriasis, vascular inflammation is observed using 18-fludeoxyglucose PET/CT (FDG-PET/CT) signal in large vessels, namely the aorta -the signals of which have a dose-response relationship to psoriasis severity (25). The FDG-PET/CT signal is believed to be derived from infiltrative macrophages residing within the vessel wall (26).…”
Section: Discussionmentioning
confidence: 99%
“…Os doentes com psoríase apresentaram um aumento significativo de inflamação em múltiplos segmentos da aorta, mesmo após ajuste para os fatores de risco cardiovascular tradicionais. Um outro estudo conduzido por Naik et al 40 avaliou a relação entre a inflamação vascular, medida por FDG-PET/ CT, através da média da razão target-to-background (TBR) aórtica, e a gravidade da psoríase, através do índice da área e gravidade da psoríase. Nesse estudo verificou-se que a gravidade da doença estava associada ao aumento da TBR, mesmo efetuando ajuste para a idade, sexo e score de risco de Framingham.…”
Section: Ateroscleroseunclassified
“…Vascular 18 F-FDG signals have also been shown to be significantly correlated with presence of traditional cardiovascular risk factors (e.g. older age, smoking, hypertension, diabetes mellitus, and hyperlipidemia) and are elevated in patients with systemic inflammatory conditions conferring increased cardiovascular risk, such as rheumatoid arthritis and psoriasis [119][120][121]. Data from the prospective Dublin Carotid Atherosclerosis Stroke Study showed that increased carotid artery 18 F-FDG uptake can identify patients with increased risk of early stroke recurrence, independent of age and stenosis severity (Figure 4a,b) [122].…”
Section: Positron Emission Tomographymentioning
confidence: 99%